Interreligious Dialogue in Malaysia: Issues of its Implementation - MOHAMAD, AHMAD; Wan Ali, Wan Zailan Kamaruddin; Ghazali, Alwani; Chang, Lee Wei; Zainol, Rosilawati (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2023)
As the world continues to evolve, problems among religious adherents have increasingly rendered the need for interreligious dialogue to achieve mutual understanding. The dialogue is crucial as it is a platform to communicate, understand, and get to know others of different backgrounds and beliefs. Nevertheless, the implementation of interreligious dialogue has led to some criticism on the credibility of its practice, especially in Islam. Therefore, this paper attempts to identify the challenges that occur throughout the implementation of Interreligious dialogue and their causes. This includes the arguments and the views of leaders or religious figures as well as intellectuals in favor or against interreligious dialogue. To do that, this study focuses on literature reviews and has discovered that the issues brought upon the implementation of inter-religious dialogue were based on a less accurate description of the actual ideas and practices. The finding also shows that not enough Interreligious dialogue modules are available and this gap must be filled with fresh perspectives to serve as a resource for future dialogues. Keywords: Issues, Criticisms, Interfaith Dialogue, Modules